Good Mates Retain Us Right: Investigating the Relationship between Mate Retention Strategies, Mate Value and Relationship Satisfaction - Salkičević, Svjetlana (Array, 2014)
Mate retention strategies are an important tool in keeping a partner, and their use is determined by mate value (MV) of the partner one is trying to keep. The type of strategy used is also dependent on MV: partners of lower MV are more prone to exhibiting strategies that are cost-inflicting for the partner, whereas benefiting strategies are used by mates of higher value. The type of strategies used inflicts relationship satisfaction (RS), and is also affected by the perceived difference in MVs. However, it is unclear how someone’s perception of their partner’s MV is related to that partner’s behavior and their own RS. To this aim, we investigated the relationship of those variables on a sample of 178 couples. Our results showed that benefit-inducing strategies were more used by and towards partners of higher MV, and are positively connected with RS. Cost-inflicting strategies were more used by and towards partners of lower MV and were negatively connected with RS. Less MV difference was positively correlated with RS and benefiting strategies, and negatively with cost-inflicting strategies. It seems that good mates use strategies that benefit their partners which, in turn, make them more valuable and, consequently, their partner satisfied.